The Effect of BHA as an Antioxidant to the Accelerated Stability Test of Snakehead Fish and Kelulut Honey Ointment - Taurina, Wintari; Andrie, Mohamad; Mukkaromah, Siti (Indonesian Journal of Pharmaceutical Science and Technology, 2025)
The ointment of snakehead fish extract and kelulut honey has a synergistic potential to boost the wound recuperation process. This ointment is formulated for topical use to be easily applied to the wound area. The ointment base used in this preparation is adeps lanae. Adeps lanae is an easily oxidized substance that can cause the preparation to become unstable. The addition of antioxidants is one way to prevent the oxidation process in the preparation. This has a look at aims to decide the impact of the addition of BHA as an antioxidant in the ointments of snakehead fish extract (Channa striata) and kelulut honey (Heterotrigona itama) at 28 days of storage with an accelerated stability test method with a temperature 40 ± 20C and RH 75 ± 5%. The ointment was made with various concentrations of BHA 0.005% (F1), 0.01% (F2), and 0.02% (F3) then tested the physical properties of the ointment and analyzed by SPSS. Results of spreadability test analysis showed an increase of the spread and significant differences between F1, F2, and F3 to F0. The adhesion test analysis results showed a decrease in the stickiness of time bonding strength and a significant difference. The test results showed a decrease in acid number on the acid number F2 and F3. Results of the organoleptic test, homogeneity, and power protection showed that all formulas have good stability. F2 is the best formula to prevent oxidization of the dosage indicated by the smallest value of the acid number.